De novo transcriptome assembly and analysis during agarwood induction in Gyrinops versteegii Gilg. seedling - Dina Hermawaty; Titis Setyobudi; Husna Nugrahapraja; Maman Turjaman; Ahmad Faizal (Scientific Reports)
Abstract Agarwood is a highly prized resinous wood produced by select members of the Thymelaeaceae plant family. Its formation in Aquilaria species has been expedited using various induction techniques, revealing insights into factors affecting the chemical constituents of artificially induced agarwood. Building on this, our research delved into the potential of another Thymelaeaceae member, Gyrinops versteegii, as an alternate agarwood source. Inoculation of juvenile G. versteegii stems with local strain of Fusarium solani successfully induced the production of sesquiterpenes and chromone compounds. On a molecular level, a de novo transcriptome reconstruction and analysis highlighted biological processes related to the plant-type hypersensitive response and DNA damage 2 days post-fungal inoculation. Notably, terpenoid biosynthesis was observed only in the group exposed to the fungus for an extended duration (28 days), where DNA damage response also played a pivotal role. Despite the inherent limitations of de novo transcriptome reconstruction, capturing only a few of sesquiterpenes biosynthesis-related genes, our findings underscore the potential of G. verteegii in producing high-quality agarwood. Future high-resolution transcriptome data could further elucidate this promising avenue.